Urgency Triage Kaki Diabetes Dalam Mencegah Kegawatan Kaki Diabetes Menjelang Tsunami Diabetes 2030 - Yusuf, Saldy (Jurnal Luka Indonesia, 2018)
Background Indonesia is one of the top ten Diabetes Mellitus (DM) countries. In 2030 it was predicted the number patients with DM will be 12.0 million. Therefore, Indonesia will experience tsunami DM. The aim of this perspective paper is to explore the urgency triage system to categorize both risk and Diabetic Foot Ulcers (DFU) status. Method This was a perspective articles in combination literature review and personal experience in clinical setting. Result There were limitations data regarding DM status in Indonesia compare other Asian countries including Japan. Interestingly Japan can be model regarding prevention approach. We also introduced a triage system to categorize both risk and DFUs status based on patient general symptoms and wound status. Conclusion The current triage system illuminate new horizon against DFU in Indonesian perspective